Evaluate the economic and environmental efficiency of land use from the perspective of decision-makers’ subjective preferences - Qingmu Su (Elsevier, 2021)
Land resources are not only the spatial carriers of social and economic development, but also the carriers of environmental and ecological services. With the accelerated urbanization, the non-coordinated development of land resources and environmental protection will restrict economic growth and the benefits of land use changes. Moreover, the economic efficiency and environmental efficiency of land use largely depend on the value judgment of the decision makers on the future human environment. Therefore, it is extremely important to achieve a win–win outcome of land development and ecological protection. In this research, a new analysis framework for land use efficiency was proposed from the perspective of decision makers' different benefit preferences. This framework uses the unexpected output of environmental pollution as a bridge to build a two-stage data envelopment analysis (DEA) model to evaluate the economic efficiency, environmental efficiency and overall efficiency of land development, and weight parameters were constructed to express decision-makers' preferences. The model not only considers the objectivity of the scores of land use efficiency, but also guarantees the subjectivity of decision-makers in land use management. This is also the biggest difference between previous studies in this study. The specific conclusions are: (I) as decision makers tend to focus on economic benefits, economic efficiency first rises and then declines. It can be seen that ignoring the problem of environmental pollution will reduce economic efficiency. (II) Generally speaking, the efficiency of compact land development (0.883) in various counties and cities in Taiwan is greater than the efficiency of expanded land development (0.737). This research can provide guidance on the distribution of land resources and the development of land space on a macro-regional scale.